Exploring orphan GPCRs in neurodegenerative diseases - Öz-Arslan, Devrim; Yavuz, Melis; Kan, Beki (Frontiers in Pharmacology, 2024)
Neurodegenerative disorders represent a significant and growing health burden worldwide.Unfortunately, limited therapeutic options are currently available despite ongoing efforts. Over the past decades, research efforts have increasingly focused on understanding the molecular mechanisms underlying these devastating conditions. Orphan receptors, a class of receptors with no known endogenous ligands, emerge as promising druggable targets for diverse diseases. This review aims to direct attention to a subgroup of orphan GPCRs, in particular class A orphans that have roles in neurodegenerative disorders, including Alzheimer's disease, Parkinson's disease, Huntington's disease, and multiple sclerosis. We highlight the diverse roles orphan receptors play in regulating critical cellular processes such as synaptic transmission, neuronal survival and neuroinflammation. Moreover, we discuss the therapeutic potential of targeting orphan receptors for the treatment of neurodegenerative disorders, emphasizing recent advances in drug discovery and preclinical studies. Finally, we outline future directions and challenges in orphan receptor research.